Populism and Woman - KOUROU, NUR SİNEM (My University, 2019)
When I saw the announcement for the winter school, I immediately felt that I want to participate in. While I am certain that you will receive many high quality applications, I will take the following paragraphs to show why I, a Ph.D. Candidate at Boğaziçi University Istanbul, am ideally placed to make a valuable contribution to the event. My PhD project aims to understand the relationship between populist mobilization and gender issue by making a qualitative analysis of the motivations for the women voters of the Justice and Development Party in Turkey. Today, all around the world -the USA, Hungary, Poland, Italy, Turkey- has been experiencing the rise of radical right wing populist parties. Thus, when my research has questioned the relationship, it also aims to deconstruct the relationship between democracy and rule of law in the reverse angle. I mean, when populism is chosen a way for holding the power, its occupation into the liberal order is inevitable such as destroying rule of law. When the populism has been defined as a democratic illiberalism, it represents the unlimited democracy’s danger clearly by the legitimacy of majority power. Additionally, the situation between the rule of law and democracy should be discussed with awareness of new actors. So, the new actor reminds that the importance of the balance and association between them when it disappeared. Rising support of women to the newly mainstreaming populist radical right wing parties has emerged as a new position in the politics of the 21st century. Therefore, being defined as illiberal democracies, one of the fields that the right-wing populist parties and government has the highest level of suppression is gender issues. When the populist radical right wing constructs the illiberal and conservative norms on the gender issue as desires of majority rules, it undermines the individual liberties, gender equality, women emancipation and progress. Therefore, the populist anti-gender perspective is one of the cases, which has rejected norms of liberal democracy through conservative ideology and populist political actions such as anti-abortion law in Turkey, 500+ subsidization in Poland or banning gender studies in Hungary. By these governments, women are defined over the family and their role within the family such as child bearing, motherhood and housewifery. By this way, their individual existence within the society have been disappeared, because of their familial recognition and connections into the state. Contrary to the aforementioned illiberal gender policies of the governments and parties, many of the populist parties and governments have received more female votes than the male ones. As in the case of Turkey women have tendency to vote the AKP/JDP more than male voters to illustrate that when the AKP’s voters’ 51% was women, 49% was man in national election in 2009 (KONDA; 2018). Based on this dilemma, my PhD project aims to answer the question of why women have a tendency to vote for radical right-wing political parties, which have anti-gender party programs? To answer this question, I will conduct qualitative research by analyzing the following three angles perspectives: The AKP’s and leaders’ discourse, political participation process of women as active member; mobilization of women as a constituency. Examining these angles will provide a fertile ground to investigate the relationship between populism and women from a multi-level perspective. Clearly, populism has risen as a challenge against the established democracies and rule of law, yet it has also negative impact on unconsolidated democracies such as Turkey, Hungary and Poland. Even though populism has more or less the same consequences those two type of the states, its impact has been felt deeply in slippery ground of unconsolidated democracies’ political and social life, as in the case of gender issue.